1993
DOI: 10.1046/j.1537-2995.1993.33293158049.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of platelet‐specific antigens among Chinese in Taiwan

Abstract: The frequencies of six platelet-specific antigens among Chinese in Taiwan are reported, which have not previously been well studied. HPA-1a (PlA1) antigen was positive in all 1100 Chinese tested. HPA-4b (Yukb) antigen was positive in all 100 persons tested. HPA-2b (Ko(a), Sib(a)) antigen was positive in 9 percent of 100 persons tested, HPA-3a (Bak(a)) in 77 percent, and NAKa in 96 percent. HPA-4a (Yuk(a)) antigen occurred in 0 percent in this study but is estimated to be present in 0.5 percent of the Taiwanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
4
16
0
Order By: Relevance
“…CD36 deficiency (Nak a-phenotype) is common among Chinese (18). We screened 2 male volunteers with CD36 deficiency in our laboratory, neither with a history of bleeding diathesis.…”
Section: P L a T E L E T -D E R I V E D M I C R O V E S I C L E S P Rmentioning
confidence: 99%
“…CD36 deficiency (Nak a-phenotype) is common among Chinese (18). We screened 2 male volunteers with CD36 deficiency in our laboratory, neither with a history of bleeding diathesis.…”
Section: P L a T E L E T -D E R I V E D M I C R O V E S I C L E S P Rmentioning
confidence: 99%
“…CD36 -mice have normal tail vein bleeding times and over many years of observation do not exhibit a bleeding diathesis. Human platelet CD36 deficiency (known as the Nak a-phenotype) is common in Asian and African populations (24)(25)(26)(27), and similar to the situation in mice, is not associated with an obvious bleeding diathesis. Recently our group, in collaboration with Podrez, Hazen, and Byzova, showed that atherogenic oxLDL binds and activates platelets in a CD36-dependent manner (28).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we discovered that there were differ ences in the frequencies of platelet-specific antigens be tween Caucasians and Orientals, with the frequency of HPA-la (P1A1) among Taiwanese being 100% [1], Although neonatal alloimmune thrombocytopenia (NAIT) occurs in frequently in our population, platelet antibodies have occa sionally been encountered during our routine blood bank procedures. The establishment of a platelet panel and spe cial platelet serological methods in our laboratory have since enabled us to perform detailed platelet serological studies.…”
Section: Introductionmentioning
confidence: 74%
“…This method has also been described in our previous study [1]. However, in the current study, a minor change was made, the platelets being fixed with 1:2,000 diluted glutaraldehyde in PBS (pH 6.0), in stead of 7% formaldehyde in PBS.…”
Section: Mixed Passive Hemagglutination Test (Mpha) [3]mentioning
confidence: 99%
See 1 more Smart Citation